Um olhar reflexivo sobre a avaliação de aprendizagem no ensino de língua portuguesa em uma escola quilombola de Moju - ESPÍRITO SANTO, Renata Ferreira do (2019)
The present work is an approach of the evaluation process in the Portuguese Language teaching of the Municipal School of Basic Education "Our Lady of the Conception", having the problem of the research to know if the process is used in a way that facilitates the National Curriculum Guidelines for Quilombola School Education in Basic Education. The National Curriculum Guidelines for Quilombola School Education in Basic Education. In addition, it has the main objective to understand the evaluation process of the teaching of the Portuguese Language of the quilombola school. A qualitative research was carried out, being defined in a case study, in which an in research was carried out, classroom observations, application of an open questionnaire and analysis of the collected data. Thus, the analysis of the data collected allowed the evaluation of the process of the quilombola student, understood as a process of information seizure investigation, which allows the teacher to identify the level of student learning, which uses the formative evaluation demonstrating knowledge about the evaluation of the teaching of the quilombola student through intervention and adaptation of the methods to their socio-cultural context. We used as a theoretical contribution Antunes (2011, 2003, 2008), Bloom (1983), Haydt (2008), Luckesi (1997, 2001, 2002, 2005, 2011), Rabelo (1998), among other authors that discuss the evaluation learning.